Identification and Characterization of New Alu Element Insertion in the BRCA1 Exon 14 Associated with Hereditary Breast and Ovarian Cancer - Ahmed Bouras (MDPI AG, 2021)
Hereditary breast and ovarian cancer syndrome (HBOC) is an autosomal dominant cancer predisposition syndrome characterized by an increased risk of breast and ovarian cancers. Germline pathogenic variants in BRCA1 are found in about 7–10% of all familial breast cancers and 10% of ovarian cancers. Alu elements are the most abundant mobile DNA element in the human genome and are known to affect the human genome by different mechanisms leading to human disease. We report here the detection, by next-generation sequencing (NGS) analysis coupled with a suitable bioinformatics pipeline, of an AluYb8 element in exon 14 of the BRCA1 gene in a family with HBOC history first classified as BRCA-negative by Sanger sequencing and first NGS analysis. The c.4475_c.4476insAluYb8 mutation impacts splicing and induces the skipping of exon 14. As a result, the produced mRNA contains a premature stop, leading to the production of a short and likely non-functional protein (pAla1453Glyfs*10). Overall, our study allowed us to identify a novel pathogenic variant in BRCA1 and showed the importance of bioinformatics tool improvement and versioning.